Validating multiplexes for use in conjunction with modern interpretation strategies. (January 2016) - Taylor, Duncan; Bright, Jo-Anne; McGoven, Catherine; Hefford, Christopher; Kalafut, Tim; Buckleton, John
Abstract: In response to requests from the forensic community, commercial companies are generating larger, more sensitive, and more discriminating STR multiplexes. These multiplexes are now applied to a wider range of samples including complex multi-person mixtures. In parallel there is an overdue reappraisal of profile interpretation methodology. Aspects of this reappraisal include 1. The need for a quantitative understanding of allele and stutter peak heights and their variability, 2. An interest in reassessing the utility of smaller peaks below the often used analytical threshold, 3. A need to understand not just the occurrence of peak drop-in but also the height distribution of such peaks, and 4. A need to understand the limitations of the multiplex-interpretation strategy pair implemented. In this work we present a full scheme for validation of a new multiplex that is suitable for informing modern interpretation practice. We predominantly use GlobalFiler™ as an example multiplex but we suggest that the aspects investigated here are fundamental to introducing any multiplex in the modern interpretation environment.